Application of Dijkstra's Algorithm to Determine the Shortest Route from City Center to Medan City Tourist Attractions - Liskedame Yanti Sipayung; Chaston Ramotto Sinaga; Angelica Claudia Sagala (Information Technology and Science (ITScience), 2023)
Tourist attractions are very interesting things to visit in an area that we are living. It is no exception when visiting the city of Medan, the tourists will visit interesting tourist spots in the city of Medan. To optimize time so that you can visit all tourist attractions in Medan City, you need to map locations so that you can create the shortest route that can be used to take all the tourist sites you want to visit in Medan City. The shortest route of a trip will shorten the travel time. Likewise in terms of seeking experts. When requesting a route from one point (start point) to another location (destination point), usually the result that comes out is the